A Study of Attitude of Secondary School Students and Teachers Towards Vocational Education (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
Vocational education prepares the students for world of work and life. The present study aims to understand the attitudes of secondary school students and teachers towards vocational education. A sample of 120 students and 60 teachers was selected from schools in Bhopal city. The students and teachers attitudes towards vocational education were measured using a five point Likert-type scale. The researcher developed the tool to measure the attitude of students and towards vocational education. From the results it wasevident that the students and teachers had favourable attitude towards vocational education. There exists no significant difference between attitude of male and female students towards vocational education. There exists no significant difference between attitude of government and private school students towards vocational education. There exists a strong positive correlation between attitude of teachers and students towards vocational education. Therefore, it is suggested that the teachers should provideappropriate orientation to the students for vocational education.